A coupled hydro-mechanical non-ordinary state-based peridynamics for the fissured porous rocks. (1st February 2021) - Shou, Yundong; Zhou, Xiaoping
Abstract: A novel coupled hydro-mechanical non-ordinary state-based peridynamics is proposed to investigate hydro-mechanical problems in fissured porous rocks. The hydraulic bond is introduced to the coupled numerical model to transfer the water flow stored in material points. The flow equations for fissured porous rocks are obtained in the framework of peridynamics. Then, the relationship between peridynamic hydraulic conductivity and classic hydraulic conductivity for one-dimensional and two-dimensional flow cases is established. Moreover, Biot's porous media theory is employed to determine the deformation caused by water pressure, which is introduced to the non-ordinary state-based peridynamic government equation. In addition, the effects of mechanical deformation and fracture on hydraulic conductivity are considered in the coupled hydro-mechanical non-ordinary state-based peridynamic model. Finally, three different numerical experiments are carried out to verify the correctness of the coupled hydro-mechanical peridynamic model proposed in this paper, and it is found that the present numerical results are in good agreement with the analytical solutions.